Navigating Student Stresses in the Interface Between Creative and Technological Competence : A Case Study in Interior Architecture : Final Report. - Smith, Dianne; Lilly, Linda (Office for Learning and Teaching, 2014)
Final report from a project which primarily aimed to gain an understanding of contemporary university students' experience of stress in a creative discipline where investigations, outcomes and critique are continually in the public gaze of peers and staff. The secondary aim was to identify situational influences that could reduce negative pressures and foster positivity. Students in Interior Architecture encounter high-stress situations due to constant professional scrutiny by staff and peers. The project applied an action research approach in order to identify insiders' perspectives (staff and students) on learning experiences, by implementing focus groups, one-on-one interviews and questionnaires. The project developed a stress scale, capturing the term used in relation to emotions experiences (negative of positive). The project also established in which situations students are particularly prone to stress. The project found that: Learning situations are not inherently negatively stressful for contemporary university students in interior architecture; Comparatively, some learning situations are more stressful than others. Where situations are negatively stressful, expectations are often involved. Where situations are negatively stressful, miscommunication was often involved. The greater inconsistency in the mechanics of a course (including for example presentation requirements, assessment requirements and grading scale, access to resources and electronic management system), the greater the level of stress that can be caused.